THE ROLE OF THE TEACHER IN THE EDUCATIONAL PROCESS - Nematulla Abdukarimovich Gulbaev; Alina Viktorovna Martsinkovskaya (Bright Mind Publishing, 2025)
The article emphasizes the role of the teacher in the educational process. In the process of teaching a teacher, based on the nature of the lessons organized with students, aspects of his activities are revealed and attention is paid to modern teaching methods.
Keywords: Education, process, lesson, student.